2013
DOI: 10.2460/javma.242.4.527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pregnancy and foaling rates after reduction of twin pregnancy via transvaginal ultrasound-guided aspiration in mares

Abstract: TUA was effective for reduction of twin pregnancy in mares, with best results achieved before gestational day 43.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 21 publications
3
27
0
3
Order By: Relevance
“…In the current study, TUA success rates showed no significant differences according to the gestational periods evaluated. This is in agreement with Klewitz et al (13) for data evaluated up to 4 weeks after TUA. However, the authors found that live foaling rate was significantly reduced when TUA was performed after day 42 (13).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, TUA success rates showed no significant differences according to the gestational periods evaluated. This is in agreement with Klewitz et al (13) for data evaluated up to 4 weeks after TUA. However, the authors found that live foaling rate was significantly reduced when TUA was performed after day 42 (13).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with Klewitz et al (13) for data evaluated up to 4 weeks after TUA. However, the authors found that live foaling rate was significantly reduced when TUA was performed after day 42 (13). Several other studies exist indicating that puncture of unicornually located twins is significantly more successful if done before day 35 of gestation (5,11).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations